Perspective Applications and Associated Challenges of Using Nanocellulose in Treating Bone-Related Diseases - Khan, Suliman; Siddique, Rabeea; Huanfei, Ding; Shereen, Muhammad Adnan; Nabi, Ghulam; Bai, Qian; Manan, Sehrish; Xue, Mengzhou; Ullah, Muhammad Wajid; Bowen, Hu (Frontiers in Bioengineering and Biotechnology, 2021)
Bone serves to maintain the shape of the human body due to its hard and solid nature. A loss or weakening of bone tissues, such as in case of traumatic injury, diseases (e.g., osteosarcoma), or old age, adversely affects the individual’s quality of life. Although bone has the innate ability to remodel and regenerate in case of small damage or a crack, a loss of a large volume of bone in case of a traumatic injury requires the restoration of bone function by adopting different biophysical approaches and chemotherapies as well as a surgical reconstruction. Compared to the biophysical and chemotherapeutic approaches, which may cause complications and bear side effects, the surgical reconstruction involves the implantation of external materials such as ceramics, metals, and different other materials as bone substitutes. Compared to the synthetic substitutes, the use of biomaterials could be an ideal choice for bone regeneration owing to their renewability, nontoxicity, and non-immunogenicity. Among the different types of biomaterials, nanocellulose-based materials are receiving tremendous attention in the medical field during recent years, which are used for scaffolding as well as regeneration. Nanocellulose not only serves as the matrix for the deposition of bioceramics, metallic nanoparticles, polymers, and different other materials to develop bone substitutes but also serves as the drug carrier for treating osteosarcomas. This review describes the natural sources and production of nanocellulose and discusses its important properties to justify its suitability in developing scaffolds for bone and cartilage regeneration and serve as the matrix for reinforcement of different materials and as a drug carrier for treating osteosarcomas. It discusses the potential health risks, immunogenicity, and biodegradation of nanocellulose in the human body.